(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article analyzes issues related to the types of procedural functions of the head of the investigative body. Additionally, problems concerning two groups of functions performed by the head of the investigative body have been thoroughly examined. Furthermore, the work of national and foreign scholars, as well as relevant legislation, has been analyzed.